Media Interaktif Patriasite untuk Pengenalan Budaya Lokal Kabupaten Bojonegoro pada Anak Usia 5 – 6 Tahun - Fadila Nanda Aulia; Ahmad Samawi; Nur Anisa (Institut Nalanda, 2024)
The aim of this research and development is to produce appropriate patriarchal The aim of this research and development is to produce appropriate patriarchal interactive media based on the criteria of being attractive, efficient and effective as a medium for introducing various local cultures in Bojoengoro Regency to children aged 5 -6 years. In fact, several educational institutions still implement local cultural learning This research aims to develop interactive media based on an educational application called